Organic Fertilizers - From Basic Concepts to Applied Outcomes 2016
DOI: 10.5772/62981
|View full text |Cite
|
Sign up to set email alerts
|

Green Manures and Crop Residues as Source of Nutrients in Tropical Environment

Abstract: Tropical areas have prevalence of soils with low fertility, which makes the management of soil fertility a necessary practice to maintain a farming system economically and environmentally sustainable. The purpose of this chapter is to demonstrate the importance of green manure and the use of crop residues as management for soil fertility. We highlight the potential of these practices to increase/sustain productivity by providing nutrients. First, we made a short review on the main factors influencing the decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 103 publications
1
9
0
Order By: Relevance
“…Soil with low fertility predominates in tropical areas, making soil fertility management essential in maintaining an economically and environmentally sustainable farming system. The use of green manures and crop residues exerts different conditioning effects on the soil; however, the main objectives of this practice in low-fertility tropical soils are to improve the cation exchange capacity (CEC) and provide nutrients such as N, P, and S. Additionally, the decomposition of residues and OM releases nutrients such as Ca, Mg, K and trace elements (Valadares et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Soil with low fertility predominates in tropical areas, making soil fertility management essential in maintaining an economically and environmentally sustainable farming system. The use of green manures and crop residues exerts different conditioning effects on the soil; however, the main objectives of this practice in low-fertility tropical soils are to improve the cation exchange capacity (CEC) and provide nutrients such as N, P, and S. Additionally, the decomposition of residues and OM releases nutrients such as Ca, Mg, K and trace elements (Valadares et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The growth of leguminous plants and their in-situ trampling at the flowering stage by tillage (plowing) or incorporation of leaves and young twigs of plants collected from another area is called green manuring. The significance of using of green manuring crops has been recognized long ago (Pieters, 1927) for its capacity to provide nitrogen (Yang et al, 2018) and enhance soil organic carbon (Ramesh and Chandrasekaran, 2004); while its multifarious effects on crop production (Fageria, 2007;Valadares et al, 2016) and their quantification in various crops and locations are getting movement afterward. The use of green manuring is more common in rice-based cropping systems and, again, in lowland or irrigated rice ecosystems (Pooniya et al, 2012).…”
Section: Green and Brown Manuresmentioning
confidence: 99%
“…Nitrogen is required for amino acid synthesis. The rhizobiamediated N fixation by legumes as well as mineralization of organic matter supplied by soil-incorporated legume green manure can both provide free amino acids as well as nitrate-N and ammonium-N for plant uptake (Weigelt et al, 2005;Valadares et al, 2016;Solangi et al, 2019). Studies by Solangi et al (2019) to evaluate P and K uptake efficiencies of various winter leguminous cover crop species reported that phosphatase and leucine-aminopeptidase (enzyme involved in the synthesis of leucine amino acids) as well as β-glucosidase and N-acetyl-glucosaminidase were significantly increased by different species of hairy vetch green manures.…”
Section: Oat Grain Proteins and Soil Carbon Nitrogen And Sulfurmentioning
confidence: 99%